FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN KELOMPOK TANI HUTAN DARI BUDIDAYA LEBAH MADU KELULUT (Trigona spp.) BINAAN BALAI TAMAN NASIONAL BUKIT TIGAPULUH DI KECAMATAN BATANG GANSAL - Yoga Yudhatama; Defri Yoza Yoza; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Kelulut honey bees are a non -timber forest product that is used as medicine, but many other benefits other than being used as a medicine for kelulut honey can be used as business development or community income. Development of kelulut honey bee cultivation by Bukit Tigapuluh National Park by forming a Forest Farmers Group. The establishment of Forest Farmers Group is one of the community empowerment activities that will be carried out by Bukit Tigapuluh National Park in Batang Gansal Subdistrict, among which are built by Forest Farmers Group, namely Jelemu Bengayauan Forest Farmers Group, Tualang Sejahtera Forest Farmers Group, and Tunas Harapan Forest Farmers Group. Honey bee farming is a side job that contributes significantly to income. In the development of kelulut honey bee farming, there are several problems with kelulut honey income differences. So we need any factors that affect the cultivation of honey bees kelulut. This study aims to determine the factors that affect the income of forest farmers constructions Bukit Tigapuluh National Park in Batang Gansal District. This study uses saturated sampling method (census) and data collection obtained through interviews, observations, and document studies. Data obtained from the research results were analyzed using qualitative descriptive analysis. The results show that the factors that influence the cultivation of kelulut honey bees on Forest Farmers Group income can be seen from the aspect of cultivation techniques, the aspect of kelulut honey bee feed, and the aspect of forestry extension. Keywords: Income of Forest Farmers Group, Kelulut Honey Bees (Trigona spp.), Bukit                     Tigapuluh National Park.